Urgency Analysis And Identification of Weaknesses In Implementation Of Accountability System Performance of Government Institutions (Sakip) Tanah Bumbu Regency 2015-2021 - Rooswandi Salem; Andi Tenri Sompa; Samahuddin Muharram (Wadah Inovasi Indonesia, 2021)
Over time, performance measurement in government agencies has changed orientation, namely performance measurement, which is input-oriented (more specifically budget), shifting to performance measurement result-oriented. This study aims to evaluate the problems and factors that are involved. Affect the effectiveness of the implementation of the Accountability System Performance of Government Institutions (SAKIP) in the Tanah Bumbu Regency government. This study also explores the classification level of implementation and the leading performance indicators in SAKIP in the SKPD Tanah Bumbu Regency to determine the obstacles in implementing SAKIP. This research is a qualitative-quantitative study (mix method) using a case study approach. The approach used is a case study approach that focuses intensively on a particular object that studies it as a case. Meanwhile, the Likert scale's quantitative approach describes the urgency in the form of tables and percentages. The data strengthened by a qualitative narrative that adapts to identifying weaknesses based on quantitative analysis. The weaknesses found in this study cover all aspects, starting from understanding and elaborating the vision and mission and strategic plans of Tanah Bumbu Regency. Mapping of performance targets, a stipulation of performance planning documents, implementation of policies, programs and activities; performance evaluation, performance control, and improved performance.